The impact of accreditation on health care quality in hospitals - Marković Petrovic, Gordana; Vuković, Mira; Jović Vraneš, Aleksandra (Vojnosanitetski pregled, 2020)
Background/Aim. Accreditation is considered to be the oldest and most widespread mechanism of independent external evaluation of health care quality and is implemented in over 70 countries worldwide. Despite numerous studies in this field, there is still no solid evidence about its impact on health care quality and patient safety. The goal of this paper was to investigate if the accreditation process has an effect on the difference in values of health care quality indicators. Methods. The study was conducted in two tertiary level health care hospitals, one accredited, the other non-accredited. Values of seven quality indicators in the period before, during and immediately after the completion of accreditation (from 2007–2015), which measure health care quality, patient safety, the efficiency and productivity of the institution, were compared. Results. Of the seven monitored quality indicators, a positive effect of the accreditation process can be attributed to a shorter length of waiting for the first scheduled health check at the institution, shorter length of waiting for the first scheduled surgical check, lower rate of patients with decubitus  as well as a decrease of the rate of hospital days per patient with acute myocardial infarction. No effect of accreditation was found on the mortality rate, mortality rate within the first 48 hours of hospitalization, and the average rate of hospital days per patient at the level of the institution. Conclusion. The process of accreditation undoubtedly intensifies activities that contribute to improving health care quality, which results in better health outcomes. Additional research in this field and new evidence about the relationship between accreditation and quality upgrading in health care institutions are required because this could motivate their managers to decide more easily to enter into this process and implement it, despite the additional efforts and financial investments associated with accreditation.
Keywords: accreditation; quality assurance, health care; health status indicators; quality improvement.